Does Low Threshold Value Use Improve Proximal Neoplasia Detection by Fecal Immunochemical Test? - Kim, Nam Hee; Yang, Hyo-Joon; Park, Soo-Kyung; Park, Jung Ho; Park, Dong Il; Sohn, Chong Il; Choi, Kyuyong; Jung, Yoon Suk (Digestive diseases and sciences, 2016)
Background Several studies have reported that the fecal immunochemical test (FIT) less sensitively detects proximal advanced neoplasia (AN) compared to distal AN. Low threshold value use may improve proximal AN detection. Aim To investigate whether FIT diagnostic accuracy for AN is different according to AN location and to compare FIT accuracy in proximal AN detection using different threshold values. Methods This retrospective study was conducted in a university hospital in Korea from June 2013 to May 2015. Out of 34,547 participants who underwent FITs, 3990 subjects aged ≥50 years who also underwent colonoscopies were analyzed. The FIT diagnostic accuracy for AN with differing locations (proximal vs. distal) and threshold values (20, 15, and 10 mcg Hb/g feces) were assessed. Results The sensitivity, specificity, positive predictive value, and negative predictive value of FIT in AN detection were 42.2, 84.3, 24.1, and 92.5 %, respectively. The FIT sensitivity for proximal AN detection was significantly lower than that for distal AN detection (32.7 and 49.0 %, respectively; P = 0.001). Lowering FIT threshold values tended to increase the sensitivity for proximal AN, whereas it significantly decreased the specificity for proximal AN. As a result, there was no significant difference in the accuracy for proximal AN detection (80.1, 79.3, and 78.1 % for 20, 15, and 10 mcg Hb/g feces, respectively; P = 0.107). Conclusions FIT was less sensitive in proximal AN detection than distal AN detection. Lowering the FIT cutoff threshold did not increase the accuracy for proximal AN detection. New biomarker development for colorectal cancer screening is required to improve proximal ACRN diagnostic accuracy.